2001
DOI: 10.1007/s11746-001-0237-8
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of papaya lipase in esterification of aliphatic alcohols a comparison with microbial lipases

Abstract: Straight-chain saturated C4 to C18 alcohols and unsaturated C18 alcohols, such as cis-9-octadecenyl (oleyl), cis-6-octadecenyl (petroselinyl), cis-9,cis-12-octadecadienyl (linoleyl), all-cis-9,12,15-octadecatrienyl (α-linolenyl), and all-cis-6,9,12-octadecatrienyl (γ-linolenyl) alcohols, were esterified with caprylic acid using papaya (Carica papaya) latex lipase (CPL) and immobilized lipases from Candida antarctica (Lipase B, Novozym, NOV) and Rhizomucor miehei (Lipozyme, LIP) as biocatalysts. With CPL, highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 27 publications
1
5
0
4
Order By: Relevance
“…Therefore, low-calorie triglycerides and other structured TAG were synthesized via papaya lipase-catalyzed interesterification of natural oils and fats with commercial purified FA or pure alkyl FA esters [14][15][16][17]. In addition, the specificity of the papaya lipase in the esterification of aliphatic alcohols with free FA was reported and compared with microbial lipases [18][19][20]. However, to the best of our knowledge, only few studies reported the alcoholysis of aliphatic alcohols with homogeneous TAG catalyzed by papaya lipase [21,22], and publications describing the enzymatic alcoholysis of natural oils and fats using papain are very rare in the literature [23].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, low-calorie triglycerides and other structured TAG were synthesized via papaya lipase-catalyzed interesterification of natural oils and fats with commercial purified FA or pure alkyl FA esters [14][15][16][17]. In addition, the specificity of the papaya lipase in the esterification of aliphatic alcohols with free FA was reported and compared with microbial lipases [18][19][20]. However, to the best of our knowledge, only few studies reported the alcoholysis of aliphatic alcohols with homogeneous TAG catalyzed by papaya lipase [21,22], and publications describing the enzymatic alcoholysis of natural oils and fats using papain are very rare in the literature [23].…”
Section: Introductionmentioning
confidence: 99%
“…Verificou-se que a lipase apresentou maior atividade de esterificação sempre em meio reacional com uma mistura de ácidos carboxílicos de cadeia curta (C4-C12) e em mistura de álcoois primários também de cadeia curta (C4-C8) 35 . Em contrapartida, foi inativa frente a uma mistura equimolar de álcoois insaturados de cadeia longa 36 (Tabela 4). Essa enzima mostrou ter preferência por ácidos insaturados, cis-5 e cis-9, quando comparados com cis-4, cis-6 ou cis-8, em reações de esterificação com 1-butanol.…”
Section: Caracterização E Aplicações Em Reação De Sínteseunclassified
“…Para essa lipase os maiores rendimentos (85%) foram para os álcoois de cadeias curtas (< C8) e os menores (22%), para os de cadeias longas (> C10) 36 , enquanto que para as lipases microbianas os rendimentos foram elevados (90-100%) para todos os álcoois (C4-16 e C18:1, C18:2, C18:3).…”
Section: Quando Comparada Com Lipases Microbianas (Lipase B Deunclassified
See 1 more Smart Citation
“…However, plant origin lipase has not or less been explored yet, although some plant extracts have been studied and showed lipolytic activities . Carica papaya latex is well known as a source of protease, some previous studies shown it has lipase activity (Giordani et al, 1991;Villeneuve et al, 1995;Mukherjee and Kiewitt, 1996;Gandi andMukherjee, 2000, Suhardi et al, 2004;Indrati et al 2004). Several studies on rice bran have also found lipase activity (Funatsu et al, 1971;Herawan, 2004, Hutomo et al, 2002.…”
Section: Introductionmentioning
confidence: 99%